Analisis Proses Rekrutmen Daily Worker pada Holiday Inn Express Baruna Bali - Ni Made Priartini; Putu Indah Rahmawati (Universitas Pendidikan Ganesha, 2020)
This research aims to determine the strategy of upgrading waiter/ss skills at Makase Restaurant. The subject of this study is Supervisor and employee of Makase Restaurant. The object of this study is a strategy to improve the skills of waiter/ss at Makase Restaurant. Data collection methods are observations, documentation and interviews. The results of this research are (1) waiter/ss constraints in serving guests at Makase Restaurant is a limitation of foreign languages because not all guests can speak English cause slow service and guest complaint. (2) the strategy used to improve the skills of waiter/ss is to provide consistent training, competency tests, and hold competitions in hotels that can affect operational smoothness, increase guest satisfaction and increase sales.